7C.01: ARTERIAL STIFFNESS IN ISOLATED OFFICE SYSTOLIC HYPERTENSION. (June 2015) - Antza, C.; Papakatsika, S.; Dimopoulos, C.; Mikoudi, K.; Stabouli, S.; Kotsis, V.
Abstract : Objective: The aim of this study was to study arterial stiffness in patients indentified as isolated systolic hypertensives. Design and method: 1056 consecutive subjects (48.6% male) aged 47.26 ± 23.4 years were included in the study. 64.7% of the subjects were never treated before for hypertension. A physician measured office BP three times in each subject using a mercury sphygmomanometer. Pulse wave velocity (PWV) was measured after 15 min of rest in the supine position. Patients were classified as having either normal or elevated systolic and diastolic BP, office isolated systolic (>140mmHg systolic and < 90 mmHg diastolic BP) and diastolic hypertensive (<140mmHg systolic and >90 mmHg diastolic BP) subjects. Results: Carotid-femoral (c-f) PWV was 8.045 ± 4.591 m/sec in patients with both normal office systolic and diastolic BP (n = 438), 11.481 ± 6.356 m/sec in patients with isolated office systolic hypertension (n = 202), 7.421 ± 5.108 m/sec in patients with isolated office diastolic hypertension (n = 60), and 9.192 ± 6.113 m/sec in patients with both elevated office systolic and diastolic BP. The difference between isolated office hypertensive subjects and those with both normal systolic and diastolic BP was 3.446 ± 0.471 (SE) m/sec (P < 0.001). The difference between subjects with both elevated systolic and diastolic blood pressure and those with both normal BP was 1.147 ± 0.389 (SE) m/sec (P < 0.05). In univariate analysis of variance age (B = 0.076, P < 0.001) and isolated office systolic hypertension (B = 1.622, P < 0.001) were independent determinants of c-fPWV. c-fPWV was found 8.688 ± 0.266 (SE) in patients with both normal office systolic and diastolic BP and 10.575 ± 0.386 (SE) m/sec in patients with isolated office systolic hypertension after adjustment for age, gender, and BMI. The difference in c-fPWV between patients with isolated office systolic hypertension and subjects with normal office systolic and diastolic BP was 1.887 ± 0.489 (SE) after adjustment for age, gender, and BMI. This difference was significant at the 0.001 level after Bonferroni's adjustment for multiple comparisons. Conclusions: Arterial stiffness was found increased in patients with office isolated systolic hypertension suggesting a role for increased office systolic BP in the pathophysiology of large arteries arteriosclerosis independent of age, gender and obesity or a role of stiffer arteries in the pathogenesis of isolated systolic hypertension.